How Personality Traits Are Related to the Attitudes Toward Forced Remote Learning During COVID-19: Predictive Analysis Using Generalized Additive Modeling - Dikaya, Liudmila A.; Avanesian, Garen; Dikiy, Igor S.; Kirik, Vladimir A.; Egorova, Valeria A. (Frontiers in Education, 2021)
Background. During the COVID-19 pandemic, universities all over the world have had to reorganize their work for remote education to ensure continuity of learning. This situation has forced both teachers and students into an atypical, very specific situation, in which they need to cope with a number of psychological factors. Meanwhile, there is a research gap in academic knowledge of the social and psychological factors that determine attitudes towards forced remote learning. Objective. To analyze the psychological traits of students in relation to their attitudes towards forced remote learning. Methods. The study assessed self-regulation and communication skills, as well thinking and learning styles of 280 students in the situation of forced remote learning. We used the methods of surveying and psychological testing for data collection. The data were analyzed in R statistical software using the regression modeling methods. Results. We found that the number of students with positive (46%) and negative (54%) attitudes towards forced remote learning during the COVID-19 pandemic was approximately equal. Using regression analysis, we identified several statistically significant associations between the interpersonal communicative skills of students (self-regulation, shyness, alienation, manipulative and cooperative communication styles) and their thinking styles (right-hemispheric and integrated), on the one hand, and their attitude to remote learning, on the other. It was also illustrated that depending on the attitude to the forced remote learning, students differ by the percentage of assimilated learning materials while studying under the lockdown. Conclusion. The results identify that success of remote learning in many ways depends on the extent to which it accommodates psychological traits of students who are forced to acquire new knowledge without traditional classroom instruction.